College Students’ Perception On The Implementation Of Digital Learning Using Flipped Learning Approach In EFL Classroom - Desi Rochmawati; Agus Efendi (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Covid-19 pandemic has spread around the world which affects many factors in human life, particularly in educational sector. It forced students to embark at digital learning. The digital learning was implemented by applying flipped learning model with the implementation of virtual conference platform and Learning Management System (LMS). This study was a mixed-methods explanatory sequential research design. Qualitative and quantitative data were analyzed to gain the data of students’ perception toward the implementation of digital learning in English class. The data were collected by observing, distributing questionnaires and doing deep interviews. The result showed that digital learning promotes self-learning, flexibilities, and trigger the creativities of students and their confidence as well. Digital learning in the form of Virtual Flipped Classroom (VFC) also ensured the learning continuity in any pandemic situation. Despite of the benefits of digital learning, there were still challenging in digital learning situation related to the internet connection support.